Promoting Mental Health and Psychological Thriving in University Students: A Randomized Controlled Trial of Three Well-Being Interventions - Seppälä, Emma M.; Bradley, Christina; Moeller, Julia; Harouni, Leilah; Nandamudi, Dhruv; Brackett, Marc A. (Frontiers in Psychiatry, 2020)
This study aimed to address the decline in mental health on U.S. university campuses by examining the effects of three interventions. University students suffer from high levels of anxiety, depression, and suicide. Counseling centers on university campuses are struggling to meet increased demand. The cost to students and universities could be buffered by offering preventative, psychoeducational, and skill-building training programs that promote mental health and psychological thriving. To date, the research literature has not yielded systematically evaluated and recommendable preventative mental health and well-being programs for university students. In a registered, randomized controlled trial, 131 university students were either placed in a non-intervention control group (N = 47) or received training in one of three 30-hour, eight-week semester-long well-being programs: SKY Campus Happiness ("SKY"; N = 29), Foundations of Emotional Intelligence ("EI"; N = 21) or Mindfulness-Based Stress Reduction (“MBSR”; N = 34). Compared to the control group and controlling for variance of baseline measurements and multiple comparisons, SKY Campus Happiness had the greatest impact, improving measures of mental health and psychological thriving, and EI showed improvement on one measure of psychological thriving. The MBSR group showed no change. Delivering SKY and EI to university students may be a cost-effective and efficient way to proactively and preventatively address mental health for university students and reduce the financial strain on universities.